Direct Reprogramming of Fibroblasts Into Smooth Muscle-Like Cells With Defined Transcription Factors—Brief Report. Issue 9 (September 2018) - Hirai, Hiroyuki; Yang, Bo; Garcia-Barrio, Minerva T.; Rom, Oren; Ma, Peter X.; Zhang, Jifeng; Chen, Y. Eugene
Abstract : Objective—: To identify the transcription factors that could contribute to direct reprogramming of fibroblasts toward smooth muscle cell fate. Approach and Results—: We screened various combinations of transcription factors, including Myocd (myocardin), Mef2C (myocyte enhancer factor 2C), Mef2B (myocyte enhancer factor 2B), Mkl1 (MKL [megakaryoblastic leukemia]/Myocd-like 1), Gata4 (GATA-binding protein 4), Gata5 (GATA-binding protein 5), Gata6 (GATA-binding protein 6), Ets1 (E26 avian leukemia oncogene 1, 5' domain), and their corresponding carboxyterminal fusions to the transactivation domain of MyoD (myogenic differentiation 1)—indicated by *—for their effects on reprogramming mouse embryonic fibroblasts and human adult dermal fibroblasts to the smooth muscle cell fate as determined by the expression of specific markers. The combination of 3 transcription factors, Myocd (or Myocd*) with Mef2C (or Mef2C*) and Gata6, was the most efficient in enhancing the expression of smooth muscle marker genes and decreasing fibroblast gene expression. Additionally, the derived induced smooth muscle-like cells showed a contractile phenotype in response to carbachol. Conclusions—: Combination of Myocd and Gata6 with Mef2C* (MG2*) could sufficiently and efficiently direct differentiation of mouse embryonic and human dermal fibroblasts into induced smooth muscle-like cells, thus opening new opportunities for disease modeling, tissue engineering, and personalized medicine. Abstract : Supplemental Digital Content is available in the text.